Acid-induced topological morphology modulation of graphitic carbon nitride homojunctions as advanced metal-free catalysts for OER and pollutant degradation. (30th September 2021) - Zhang, Hua-Wei; Lu, Yi-Xin; Li, Bo; Huang, Gui-Fang; Zeng, Fan; Li, Yuan-Yuan; Pan, Anlian; Chai, Yi-Feng; Huang, Wei-Qing
Graphical abstract: Highlights: A controllable acid-induced molecular self-assembly route is first proposed to prepare hierarchical CN homojunction. The topological morphology of CN homojunction can be easily adjusted. The hierarchical CN homojunction endows a synergistic effect of active sites, charge transfer and separation. The optimized CN homojunction shows superior OER activity and high ability for pollutant degradation. Abstract: Topological morphology that dominates the surface electronic properties of nanostructures plays a key role in producing desired materials for versatile functions and applications in many fields, but its modulation for specific functions remains a big challenge. Herein, we report an acid-induced method to prepare S-doped graphitic carbon nitride/graphitic carbon nitride (S-CN/CN) homojunction by simply pyrolyzing a supramolecular precursor synthesized from melamine and H2 SO4 . The topological morphology and electronic structure of CN homojunction can be easily adjusted only by changing the ratio of raw materials. Moreover, the topological morphology of S-CN/CN homojunction can be further adjusted from hollow cocoon to 2D nanosheets by changing the annealing conditions. The optimized S-CN/CN homojunction shows highly efficient in charge transfer and separation and exhibits superior OER activity and high ability to degrade organic pollutants. Impressively, S-CN/CN nanosheets only demand low overpotential of 301 mV to drive a current density of 10 mAcm −2 in 1 M KOH media, and the corresponding Tafel slope is only 57.71 mV/dec, which is superior to the most advanced precious metal IrO2 catalyst. Moreover, under visible light irradiation, its photodegradation kinetic rate of RhB is 2.38, which is 47.6 times higher than that of bulk CN. This work provides useful guidance for designing and developing efficient multifunctional metal-free catalysts.